The Implementation of the Independent Curriculum at SMA Negeri 1 Semendawai Suku III, East OKU Regency - Sundari, Sundari; Arafat, Yasir; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2024)
This research aims to determine how the Merdeka Curriculum is implemented at SMA Negeri 1 Semendawai Suku III OKU Timur, what obstacles are encountered, and what solutions are taken to overcome these obstacles. This research uses a qualitative research method using a phenomenological approach. Data analysis was carried out by describing the results of the interview through sentences structured with scientific explanations and also carrying out analysis using a Likert scale on the data obtained from the research instrument. Based on the results of interviews with the perpetrators of implementing the Merdeka Curriculum, in this case, the principal, teachers, and students, show that the Merdeka Curriculum has been implemented thoroughly at SMA Negeri 1 Semendawai Suku III OKU Timur. The results of the Likert scale analysis of the implementation of the Merdeka Curriculum and the Ministry of Education, Culture, Research and Technology’s intervention in Sekolah Penggeraks also show that the Merdeka Curriculum has been implemented very well in schools. The obstacles found during the implementation of the Merdeka Curriculum were that online training had not become a habit for teachers so it felt difficult, limited modules, changes in curriculum structure, limited digital-based learning facilities, and the existence of a project to strengthen the profile of Pancasila students, which is a new science. Then the solution taken to overcome these obstacles is to carry out online training results for all teachers, through learning communities together with teachers creating teaching modules and dissecting curriculum structures, providing digital-based learning facilities using cellphones in learning, and implementing projects with several strategies, reflect and evaluate to improve the quality of implementation.